Host genotype and age shape the leaf and root microbiomes of a wild perennial plant - Maggie R. Wagner (Nature Portfolio, 2016)
Laboratory-based studies of the effect of plant genotype on plant microbiome composition often do not consider the influence of environmental heterogeneity. Here, Wagner et al. use a large-scale field experiment to assess the extent of host genetic and environmental factors on the microbiome of Boechera stricta.